Analysis of Exosomal miRNA and Hepatic mRNA Expression in the Dysregulation of Insulin Action in Perimenopausal Mice - Yu Yang; Yu Chen; Changju Liu; Su Wang; Yijing Zhao; Wen Cao; Kun Wang (Journal of Diabetes Research)
Conclusion: The perimenopausal period acts as a potential factor in introducing insulin resistance as evidenced by impaired insulin action and altered expression profiles of exosomal miRNAs and hepatic genes. The present study contributes to the understanding that abnormal cargos carried by plasma exosomes, such as miRNAs, may be related to altered expression of the corresponding genes in the liver and abnormal insulin response.